1999
DOI: 10.1172/jci8082
|View full text |Cite
|
Sign up to set email alerts
|

Asialo GM1+ CD8+ T cells play a critical role in costimulation blockade–resistant allograft rejection

Abstract: Simultaneous blockade of the CD40 and CD28 costimulatory pathways is an effective treatment strategy to promote allograft acceptance but does not lead to indefinite allograft survival. The immune mechanisms responsible for costimulation-independent rejection are not defined. Here we have studied the rejection responses of murine C57BL/6 recipients, which we show to be relatively resistant to inhibition by combined CD40/CD28 blockade. We demonstrate that asialo GM1 + CD8 + cells play a critical role in this cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
295
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(316 citation statements)
references
References 49 publications
(41 reference statements)
17
295
3
Order By: Relevance
“…The resistance to the effects of costimulatory blockade was alloantigen specific in that B10.A DST/aCD40L was highly effective in the presence of T cells primed to an entirely separate set of alloantigens (Table 1). Our studies confirm previously published findings that naïve CD8 π T cells (28)(29)(30)(31), T cells primed to viral antigens (32,33), and in some cases CD4 π T cells (21,34) can be resistant to the effects of costimulatory blockade. DST/aCD40L fully prevented the expansion and activation of the alloreactive T cells in naïve animals transplanted with B10.A hearts (associated with prolonged graft survival, Figure 2).…”
Section: Discussionsupporting
confidence: 92%
“…The resistance to the effects of costimulatory blockade was alloantigen specific in that B10.A DST/aCD40L was highly effective in the presence of T cells primed to an entirely separate set of alloantigens (Table 1). Our studies confirm previously published findings that naïve CD8 π T cells (28)(29)(30)(31), T cells primed to viral antigens (32,33), and in some cases CD4 π T cells (21,34) can be resistant to the effects of costimulatory blockade. DST/aCD40L fully prevented the expansion and activation of the alloreactive T cells in naïve animals transplanted with B10.A hearts (associated with prolonged graft survival, Figure 2).…”
Section: Discussionsupporting
confidence: 92%
“…Novel immunotherapeutic reagents, such as CTLA4Ig or anti-CD154, have been extremely effective in specifically blocking T-cell responses in vitro (24)(25)(26) and inducing long-term survival of organ and tissue allografts (33,35,(58)(59)(60). Notably, studies by Larsen and colleagues provided compelling evidence for the importance of CD28/ B7 and CD154/CD40 in CD4π T-cell-mediated skin allograft rejection (24,37). However, although initial studies in rodents supported an essential role for CD28/B7 and CD154/CD40 interactions in the allograft setting, an increasing number of exceptions have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies confirmed that combined blockade specifically blocked CD4π T-cell-mediated allograft reactions (37). To determine whether CD4π T cells restricted to direct antigen presentation were susceptible to tolerance induction via costimulatory blockade, we used an adoptive transfer system in which B6.RAG-1-/-mice were reconstituted with B6 aBM12 TCR Tg T cells.…”
Section: Co-stimulatory Blockade Does Not Prevent the Rejection Of DImentioning
confidence: 99%
See 2 more Smart Citations